Effect of pipe materials on thermal reduction in earth air heat exchanger - Nur Hasmiza , Yusof (2013)
Global warming and the excessive emission of CO 2 contributed to the increase of temperature in the earth's atmosphere. The increase of the earth's temperature thus leads to the reduction in the thermal comfort. Air conditioner are often used to induced cooling to building interior, however the concern over CO 2 emission and carbon footprint lead to the invention of a more environmental friendly cooling system such as Earth Air Heat Exchanger (EAHE). EAHE is a system that provides cooling by driving hot air from the environment through pipe buried and dissipates heat through soil underground. The efficiency of the system is highly influenced by several factors including pipe materials, length, and type of soils and depth of pipe buried. In this study, a simple small scale EAFIE system was designed and constructed to evaluate the thermal reduction efficiency of different pipe materials. Two different types of pipe materials of similar design were tested namely, polyvinyl chloride (PVC) pipe and Galvanized iron (GI) pipe. The tests results indicated that material having greater thermal conductivity provide better thermal reduction efficiency. The maximum reduction in temperature of 7°C was observed using GI pipe whereas, a maximum of 4°C was observed for the PVC pipe. The use of material having higher density, higher specific heat capacity and higher thermal conductivity provides better thermal reduction efficiency for an EAHE system.